Isolation of Campylobacter and Salmonella from houseflies (Musca domestica) in a university campus and a poultry farm in Selangor, Malaysia - Choo, Li Chen; Abdul Aziz, Saleha; Wai, Soe Soe; Nordin, Fauziah (Malaysian Society of Parasitology and Tropical Medicine, 2011)
Insects, in particular house flies and cockroaches, have been shown to be associated with the spread of pathogens in livestock farms and in human disease outbreaks: among these pathogens are salmonellae and campylobacters. A total of 60 flies were caught in three locations: an animal teaching facility and a cafeteria in a university campus, and a poultry farm. Five percent (5%) and 13.3% of flies sampled were found to carry Campylobacter and Salmonella, respectively.